Locus of control and performance appraisal - John S. Heywood; Uwe Jirjahn; Cornelia Struewing (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2016)
This work contributes to the literature demonstrating an important role for psychological traits in labor market decisions. We show that West German workers with an internal locus of control sort into jobs with performance appraisals. Appraisals provide workers who believe they control their environment a tool to demonstrate their value and achieve their goals. We confirm that workers who are risk tolerant also sort into jobs with performance appraisals but explain why the influence of the locus of control and risk tolerance should not be additive. We demonstrate this by estimating a routinely large and significantly negative interaction in our sorting equations. We also show that important patterns of sorting are revealed only when taking into account the interaction of locus of control and risk tolerance.
Keywords: D03; J33; M52; 330; locus of control; risk attitude; performance appraisal; performance pay; sorting; extrinsic rewards; intrinsic motivation